Pharmacokinetic study of artemether-lumefantrine given once daily for the treatment of uncomplicated multidrug-resistant falciparum malaria - Ashley, E; Stepniewska, K; Lindegardh, N; Mcgready, R; Annerberg, A; Hutagalung, R; Singtoroj, T; Hla, G; Brockman, A; Proux, S; Wilahphaingern, J; Singhasivanon, P; et al. (2007)
Background: Adherence to antimalarial drug regimens is improved by simple dosing. If the fixed antimalarial drug combination artemether-lumefantrine (AL) could be given once daily, this should improve adherence and thus effectiveness and lower the risk of selecting for resistance. Methods: In an open randomized study, 43 patients with uncomplicated falciparum malaria were given equivalent doses of AL with 200 ml flavoured milk either as the conventional twice-daily regimen or as a single daily dose for 3 days. The primary end point was a comparison of the areas under the plasma lumefantrine concentration-time curves (AUC). Secondary end points were the day 42 polymerase chain reaction (PCR)-adjusted cure rates and the tolerability profiles. Results: Lumefantrine pharmacokinetic profiles were obtained for 36 patients. The AUC of the once-daily regimen was 30% lower than that in the conventional regimen (P = 0.011) with a median (range) value of 306 (114-5781) μg/ml h, compared with 432 (308-992) μg/ml h. There was no significant difference in the peak plasma concentrations reached. PCR-adjusted cure rate estimates at day 42 of follow-up were 94% (95% CI: 84-100) in the six-dose arm and 85% (70-100) in the three-dose arm (P = 0.3). Conclusion: Artemether-lumefantrine efficacy is reduced by once-daily dosing, because absorption of lumefantrine is dose limited. At currently recommended doses, this antimalarial should be given twice daily in a 3-day regimen, with food containing fat. © 2007 Blackwell Publishing Ltd.